Integrasi antara Dwelling Time dan Bongkar Muat Peti Kemas Pelabuhan Tanjung Priok - Ricardianto, Prasadja; Suhalis, Adenan; P. Sirait, David (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2018)
The research objective is to determine the integration between waiting times for dwelling time and loading unloading container of container terminals at Tanjung Priok Port. The research method used in this study was qualitative descriptive. The five container terminals studied at Tanjung Priok port are the Jakarta International Container Terminal, Koja, NIPCT1 container terminal, Mustika Alam Lestari and Terminal 1 New Port Container. The research problem is whether the reduction in Dwelling Time will be able to increase loading unloading Container capacity at container terminals at Tanjung Priok Portor not. The result shows that there is a positive integration of Dwelling Time specifically for loading and unloading imported containers in Tanjung Priok Port and is categorized as very high, with an average duration of seven years was 5.5 days. The results of this study are expected to be able to recommend how the decline in Dwelling Time could increase loading and unloading container capacity of container terminals at Tanjung Priok Port.